2021
DOI: 10.53801/ijms.v1i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-faktor yang Mempengaruhi Partisipasi Ibu Membawa Balita ke Posyandu RW 038 Bojong Rawalumbu

Abstract: Latar Belakang: Balita merupakan golongan yang rentan terhadap masalah kesehatan. Gangguan kesehatan yang terjadi pada balita mempengaruhi pertumbuhan dan perkembangan baik pada masa balita maupun masa berikutnya. Tujuan: Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang mempengaruhi partisipasi ibu membawa balita ke Posyandu RW 038 Bojong Rawa Lumbu Bekasi. Metode: Penelitian ini dilakukan pada 35 orang responden, menggunakan desain penelitian chi-square. Sampling menggunakan total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…This research is in line with the study conducted by Simamora (2021) at the Onan Ganjang Humbang Hasundutan Health Center; based on the results of his study, it was found that there was no relationship between the mother's occupation and the completeness of immunization in infants and toddlers with a p-value of 0.742. Results of research conducted by Manurung (2021) show that as many as 252 people (93.3%) did not work, and 18 people worked (6.7%), with p = 0.454, where p>0.05, which means there is no significant relationship between work and the level of participation mothers of toddlers to posyandu.…”
Section: Babies At the Sadabuan Health Centermentioning
confidence: 95%
“…This research is in line with the study conducted by Simamora (2021) at the Onan Ganjang Humbang Hasundutan Health Center; based on the results of his study, it was found that there was no relationship between the mother's occupation and the completeness of immunization in infants and toddlers with a p-value of 0.742. Results of research conducted by Manurung (2021) show that as many as 252 people (93.3%) did not work, and 18 people worked (6.7%), with p = 0.454, where p>0.05, which means there is no significant relationship between work and the level of participation mothers of toddlers to posyandu.…”
Section: Babies At the Sadabuan Health Centermentioning
confidence: 95%
“…Ibu balita akan kecil kemungkinannya untuk mengunjungi posyandu jika pengetahuannya kurang mengenai hal tersebut (Mawarti et al, 2020). Sejalan dengan penelitian Manurung & Istiani (2021), dimana pengetahuan ibu berhubungan dengan partisipasi ibu dalam membawa balitanya ke posyandu, terlihat dari hasil penelitian bahwa ibu yang memiliki pengetahuan baik cenderung partisipasinya baik sedangkan ibu yang memiliki pengetahuan kurang cenderung partisipasinya kurang.…”
Section: Hubungan Pengetahuan Dengan Partisipasi Ibu Ke Posyanduunclassified